Multifarious properties of Bunsenite nanosphere NiO using coprecipitation method. (2020) - Revathy, M.S.; Suman, R.; Dhanpal Jayram, Naidu; Geetha, D.; Chitravel, T.
Abstract: Future applications in energy storage are greatly dependent on a material with multifunctional property. In this respect transition metal oxide has shown special attention, especially nickel oxide. A unique synthesis (coprecipitation) and multifaceted properties of NiO has been studied systematically. The result from XRD confirms Bunsenite structure having average size of crystallite ∼ 30 nm, lattice strain from W-H plot is ∼ 0.00255 along with other structural parameters are reported. The electron density distribution profile of Ni-O was computed using Rietveld method. Particle size from SEM was about 52 nm, peak at 419 cm −1 of FTIR confirms Ni-O stretching frequency and band gap of 2.95 eV are all confirmation for fine crystallinity of the prepared product under 600 °C calcination. 2.6102 m emu Saturation magnetization (Ms ), Coercivity (Hc ) of 198.35 Gauss and Retentivity (Mr) 55.172 μemu affirms paramagnetism from VSM study. The two magnon band intensity in raman spectra decreases rapidly for smaller crystallite size. This effect was clearly observed in the decrease of antiferromagnetic spin correlations and lead to paramagnetic phase. Electrochemical Impedance spectroscopy calculations illustrated aphase angle of 86° which indicates the capacitive behaviour.